Immediate Bilateral Breast Reconstruction Using Abdominally Based Flaps: An Analysis of the Nationwide Inpatient Sample Database - Holoyda, Kathleen A.; Simpson, Andrew M.; Ye, Xiangyang; Agarwal, Jayant P.; Kwok, Alvin C. (Journal of Reconstructive Microsurgery, 2019)
Background Bilateral mastectomy rates are increasing in the United States. The abdomen is the most common harvest site for autologous reconstruction. Nationwide data were examined to determine differences in hospital charges, length of stay (LOS), and early postoperative complications following immediate bilateral pedicled transverse rectus abdominis myocutaneous (pTRAM), free TRAM (fTRAM), deep inferior epigastric perforator (DIEP), and superficial inferior epigastric artery (SIEA) perforator flaps and were compared with unilateral reconstruction.Methods Patients who underwent immediate bilateral breast reconstruction using a single method of abdominally based reconstruction were identified using the 2009 to 2014 Nationwide Inpatient Sample Database. Outcomes included total hospital charges, LOS, and immediate postoperative complications.Results We identified 13,348 cases of bilateral mastectomy with a single type of immediate bilateral autologous flap reconstruction. The majority were bilateral DIEP flaps. Mean total cost for bilateral pTRAM, fTRAM, DIEP, and SIEA flaps was US $21,886.80, US $28,839.40, US $30,051.30, and US $33,784.90, respectively (p < 0.0001). Mean LOS for bilateral pTRAM, fTRAM, DIEP, and SIEA was 4.3, 4.9, 4.5, and 5.4 days, respectively (p = 0.0002), and hematoma rates were 1.93, 2.61, 3.68, and 16.59%, respectively, (p = 0.0001), whereas return to the operating room for vascular anastomosis revision was 0, 1.63, 1.99, and 19.07%, respectively (p < 0.0001). Cost is less for unilateral pTRAM, fTRAM, and DIEP flaps (p < 0.0001). LOS is shorter for unilateral fTRAM versus bilateral (p < 0.0001). No differences were appreciated between unilateral and bilateral hematoma and reoperation rates for any reconstruction (p > 0.1).Conclusion Immediate complication rates were higher in bilateral free flaps compared with bilateral pedicled flaps. pTRAM and fTRAM flap reconstructions are still performed frequently with acceptable immediate results without considering long-term morbidity, aesthetics, and abdominal muscle function. Bilateral SIEA free flaps were associated with significantly higher total cost, LOS, and complication rates compared with other groups. Complications were similar between unilateral and bilateral reconstruction procedures. While cost is significantly greater for bilateral procedures compared with unilateral pTRAM, fTRAM, and DIEP flaps, it is not doubled.
Keywords: breast reconstruction; autologous; bilateral